1990
DOI: 10.1159/000235188
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Suppressor Cell Activity in Normal Peripheral Blood Mononuclear Cells by Sera from Predialytic Uremic Patients

Abstract: Normal peripheral blood mononuclear cells (PBMC) were primed with sera from 22 predialytic uremic patients, normal sera, concanavalin A, or both. Their suppressive activity was subsequently tested on fresh phytohemagglutinin-stimulated allogeneic responders (i.e., genetically unrelated to either primed cell or sera donors). Uremic serum induced suppressor cell activity in the normal PBMC. No correlation was found between serum urea/creatinine levels and their effects on suppressor cell activity. The induced ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…[33] demonstrated that prolonged treatment of mice with IL-I results in many pathological alterations, including massive release of corticosterone which causes splenic and thymic athrophy. Therefore, in addition to many immunosuppressive factors found in uraemic serum [34], activation of hypolhalaniic-pituilary-adrcnal axis due to persistently stimulated production of TN F-a and other monokines by haemodiaiysis treatment may underly impaired immunity in dialyscd patients.…”
Section: Discussionmentioning
confidence: 99%
“…[33] demonstrated that prolonged treatment of mice with IL-I results in many pathological alterations, including massive release of corticosterone which causes splenic and thymic athrophy. Therefore, in addition to many immunosuppressive factors found in uraemic serum [34], activation of hypolhalaniic-pituilary-adrcnal axis due to persistently stimulated production of TN F-a and other monokines by haemodiaiysis treatment may underly impaired immunity in dialyscd patients.…”
Section: Discussionmentioning
confidence: 99%